Podocyte Detachment Is Associated with Renal Prognosis in ANCA-Associated Glomerulonephritis: A Retrospective Cohort Study. Issue 15 (April 2016) - Zou, Rong; Wang, Su-xia; Liu, Gang; Yu, Feng; Chen, Min; Zhao, Ming-Hui
Abstract : Abstract: The prognosis of antineutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (ANCA-GN) is unfavorable despite immunosuppressive therapy. It has been suggested that the loss of podocytes is a hallmark of progressive kidney disease. However, it is unclear about podocyte injuries and their predictive values on the prognosis in ANCA-GN. Therefore, the current study aimed to investigate the podocyte injury in renal histopathology and its association with renal prognosis of patients with ANCA-GN. A total of 170 patients with ANCA-GN were recruited in this study. Morphometric investigation of podocytes by electron microscopy including foot process width (FPW), podocyte density per glomerulus (Nv), and glomerular basement membrane (GBM) width were measured and calculated in ANCA-GN patients. Cox regression analysis was used to analyze the association between podocyte injuries and prognosis of patients with ANCA-GN. Foot processes broadening, podocyte detachment, and GBM thickening could be observed in electron micrographs in the specimens of 158/170 (92.9%), 142/170 (83.5%), and 150/170 (88.2%) patients, respectively. Compared with normal controls, FPW and GBM width in ANCA-GN patients was significantly higher (1269.39 ± 680.19 vs 585.81 ± 77.16, P  = 0.004; 668.23 ± 208.73 vs 354.23 ± 52.70, P  = 0.000, respectively), while the podocyte density was significantly lower (55.90 ± 36.32 vs 255.23 ± 47.29, P  = 0.000). The podocyte density was independently associated with the recovery of renal function in logistic regression analysis (OR, 1.083; 95% CI, 1.025–1.440; P  = 0.005). Furthermore, multivariate analysis revealed that podocyte density was an independent predictor of end-stage renal disease (ESRD) (model A: HR, 0.950; 95% CI, 0.919–1.982; P  = 0.002; model B: HR, 0.953; 95% CI, 0.922–0.985; P  = 0.004). Podocyte structural damage and detachment occurred frequently in patients with ANCA-GN. Moreover, podocyte detachment was an independent predictor of renal outcomes. Abstract : Supplemental Digital Content is available in the text